2021
DOI: 10.3390/designs5030057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sawdust Particle Sizes on the Physico-Mechanical Properties of Unfired Clay Blocks

Abstract: Sawdust, which is a waste/by-product of the wood/timber industry, can be utilised as a valuable raw material in building material production due to its abundance and low cost. However, the application of sawdust in the manufacture of unfired clay blocks has received little investigation. Furthermore, the impact of different sawdust particle sizes on the properties of unfired clay blocks has not been studied. Therefore, this study screened sawdust at three different particle sizes: SP-a (212 μm < x < 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Figure 6 shows the sawdust waste from word working operation of sawing, milling, and sanding school furniture. Sawdust is organic waste produced during the mechanical reduction of wood into numerous shapes and sizes [26]. Sawdust is an organic waste product created when wood is mechanical milled into different sizes and forms [27].…”
Section: Sawdustmentioning
confidence: 99%
“…Figure 6 shows the sawdust waste from word working operation of sawing, milling, and sanding school furniture. Sawdust is organic waste produced during the mechanical reduction of wood into numerous shapes and sizes [26]. Sawdust is an organic waste product created when wood is mechanical milled into different sizes and forms [27].…”
Section: Sawdustmentioning
confidence: 99%
“…According to Sun et al [18], there is limited research done on the stabilization of expansive soils using sawdust; and some research can be found on the use of this natural fiber in the elaboration of structural elements such as adobes [70,71], making evident the social, economic and environmental sustainability of building materials and soils improved with agricultural waste and by-products [72].…”
Section: Of 25mentioning
confidence: 99%
“…200). Regarding the investigations that used powder sawdust [1,8,36,48,72,95,[108][109][110], it was observed that these were screened with sieves of openings between 4.75mm and 0.42mm (Sieve No. 4 and Sieve No.…”
Section: Fiber Length and Sizementioning
confidence: 99%
“…Due to the physical characteristics of walnut shell (density, compressive strength, inelasticity, etc. ), it is ground and broken to make building materials by filling and mixing, as well as filler to produce modified composite materials (Salasinska et al, 2018;Jannat et al, 2021). Additionally, due to the porosity of walnut shell, it is used as a biological adsorption material and its properties were tested, demonstrating that industrial wastewater can be treated, recycled, and utilized through water treatment methods (Kerrou et al, 2021).…”
Section: The Environmental Impact Of Walnutmentioning
confidence: 99%